2013
DOI: 10.1016/j.expthermflusci.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of spreading molten metal drops deposited by fusion

Abstract: An experimental approach is presented in order to study the evolution of the spreading of a macro-drop of liquid metal. The objective of this work is to supply qualitative and quantitative information during the deposit of liquid metal in static pulsed Gas Metal Arc Welding (P-GMAW). The experimental results are analyzed in the light of dimensionless numbers in order to identify the involved physical mecanisms and appreciate the heat and mass effects on the behavior of such a macro-drop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Similar research works can also be found in high temperature process, such as Pulsed Gas Metal Arc Welding (P-GMAW) where a centimeter metal liquid pool is supplied by a millimeter liquid metal droplet (Fig. 1) [8]. It was shown that the gas-liquid-solid line motion was modified with different process parameters and shielding gas.…”
Section: Macro-drop Formation In Stationary P-gmawmentioning
confidence: 79%
See 3 more Smart Citations
“…Similar research works can also be found in high temperature process, such as Pulsed Gas Metal Arc Welding (P-GMAW) where a centimeter metal liquid pool is supplied by a millimeter liquid metal droplet (Fig. 1) [8]. It was shown that the gas-liquid-solid line motion was modified with different process parameters and shielding gas.…”
Section: Macro-drop Formation In Stationary P-gmawmentioning
confidence: 79%
“…The pur-pose of the paper is to investigate the wetting of liquid Fig. 2 Evolution of the base radius of the macro-drop with time [8]. In first time (t < 0, 5 s), the growth of radius is fast.…”
Section: Macro-drop Formation In Stationary P-gmawmentioning
confidence: 99%
See 2 more Smart Citations
“…One point is assimilated to a spherical cap with a radius R deposit . Previous studies have shown the complex relationship that can exist between process parameters and the geometry of the spherical cap [8]. The radius R deposit depends on the quantity of mass and the base radius of the spherical cap.…”
Section: 6n/m Volumetric Massmentioning
confidence: 99%